2006
DOI: 10.1038/sj.bjc.6603253
|View full text |Cite
|
Sign up to set email alerts
|

Frequent gain of the human telomerase gene TERC at 3q26 in cervical adenocarcinomas

Abstract: The level of genomic amplification of the human telomerase gene TERC, which maps to chromosome band 3q26, was determined in primary cervical adenocarcinomas. Interphase nuclei prepared from archival material of 12 primary cervical adenocarcinomas, eight of which were human papillomavirus positive, were hybridised with a triple colour probe set specific for centromeres of chromosomes 3 and 7 and the TERC gene. We observed high proportions of nuclei with increased absolute copy numbers for TERC in all tumours (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
(43 reference statements)
1
35
0
3
Order By: Relevance
“…observed in various tumors (38)(39)(40), and it may be one mechanism of increased hTR expression in the tumors. More recently, a viral form of telomerase RNA (vTR) with 88% homology to chicken telomerase RNA was found to be encoded by oncogenic strains of Marek's disease virus (MDV) but not by nononcogenic MDV strains (41).…”
Section: Discussionmentioning
confidence: 99%
“…observed in various tumors (38)(39)(40), and it may be one mechanism of increased hTR expression in the tumors. More recently, a viral form of telomerase RNA (vTR) with 88% homology to chicken telomerase RNA was found to be encoded by oncogenic strains of Marek's disease virus (MDV) but not by nononcogenic MDV strains (41).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that our study had some limitations, such as the small number of cases. To obviate this drawback, further prospective investigations with long-term follow-up will be necessary, in view of the possible introduction of hTERC FISH analysis into decision-making algorithms [44,45,46,47,48,49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…In other recent finding in different grouping of laryngeal lesions produced by Liu et al, (2012) they stated a significant elevated percentage of amplified TERC gene in moderate dysplasia, severe dysplasia, carcinoma in situ and invasive carcinoma compared to normal epithelium and mild dysplasia (p<0.0001). Moreover, Andersson et al, (2006) showed TERC gene amplification in cervical adenocarcinomas with absolute mean copy number ranged between 2.3 and 5.2 comparable to the mean of cervical adenocarcinomas without infection of human papillomavirus (HPV was 3.3). It has to be taken into account that all these mentioned TERC gene amplification studies were done in the solid tumours.…”
Section: Discussionmentioning
confidence: 99%